Efficacy of Health Belief Model in improving Exercise Behaviors to Prevent Diabetes Mellitus Among Mosul University Employees - Farouk Mohammed Nour, Mohammed Qassim Baktash, (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetes is a serious public health problem, and exercise plays an important role in preventing it. The purpose of this study is to determine the efficacy model of Health belief-based health education in improving exercise behaviors among Mosul University employees to prevent Diabetes disease. This study used an experimental design by employing a randomized control approach. The study comprised 81 individuals selected by using a simple random sampling method from five colleges of Mosul University. The sample is divided into two groups: the experimental (41) subjects and the control group (40) individuals. The data is gathered three times (T1, T2, and T3) by adopting the exercise health belief model scale. The study revealed that the sample’s mean age (SD) is 45.26 (SD = 8.59) and most of the participants are male (59.3%) and have bachelor’s degree certificates (40.7%). On the other hand, the study indicated a significant change in participants’ perceived seriousness, F (2, 79) = 9.265, P < .000, perceived benefits of exercise in preventing diabetes, F (2, 79) = 7.868, P < .001, perceived barrier F (2,79) = 7.643, p = 0. 001. The Bonofonei test proved that the change in participants' beliefs is related to the experimental group. This study is clinically important because it shows the role of health education in enhancing some beliefs related to exercise and its role in Diabetes prevention.